Financial Sustainability of Small Farmer Cooperative (SFC) in Mid-Western Region of Nepal - Tiwari, Liladhar; Nepal, Govind (Journal of Advanced Academic Research, 2018)
This article is based on Financial Sustainability of Small Farmers Cooperative (SFC) in Mid-Western of Nepal. It attempts to provide the practices and their impacts of financial sustainability of SFC. As the cooperative movement originated from the philosophy of cooperation and later developed as a powerful tool to support to improve socio-economic position of resource poor, vulnerable, members of the lower caste people, women, labors and peasants, the SFC functions with the guiding philosophy of group principle, self-help development and institutionalization of networks at the grassroots level to reduce the scarcity. This study applied a descriptive and analytical research design using both primary (observation; questionnaires, focused group discussion) and secondary (Department of Cooperative (DoC), Central Bureau of Statistics (CBS), and National Cooperative Federation of Nepal (NCF/N and annual report of sampled cooperatives) sources of data. After the analysis and interpretation of data, a number of contributions were found such as saving collection, credit investment, socio-economic development etc. The SFCs were found to be guided by self-governing norms and shares were issued to the members who are empowered with one member one vote for the general assembly purpose. The institutions function for socio-economic development with the strong policy of being apolitical and unbiased with no discrimination of any kind on religion and gender basis. The socio-economic position of cooperative members has changed through income generating programs. This study is concentrated on perception study of the financial sustainability of Small Farmer Cooperative (SFC) for the economic as well as financial development.